Forensic Monitoring Project Report: Donji Rujani Exhumation and Borovaca Surface Collection Republika Srpska Commission on Missing and Tracing - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Connor, Melissa The Republika Srpska Commission on Missing and Tracing recovered no remains on 11 June 1998 at Donji Rujani. Surface remains of a single individual were recovered from Borovača. Place of Exhumation: Donji Rujani Exhumation Site: Donji Rujani, Borovača Date of Exhumation: 11 June 1998 Minimum Number of Exhumed Individuals: 001